Micro/Nano Devices for Chemical Analysis - Manabu Tokeshi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Since the concept of micro total analysis systems (µ-TAS) has been advocated, various kinds of micro/nano devices have been developed by researchers in many fields, such as in chemistry, chemical engineering, mechanical engineering, electric engineering, biology, and medicine, among others. The analytical techniques for small sample volumes, using the micro/nano devices, heavily impacted the fields of biology, medicine and biotechnology, as well as analytical chemistry. Some applications (DNA analysis, point-of-care testing (POCT), etc.) are already commercially available, and various applications will soon be put into practical use. In this Special Issue, we focus on chemical and biochemical analyses (analytical and sensing techniques) using the various types of the micro/nano devices, including micro/nanofluidic devices, paper-based devices, digital microfluidics, and biochip (DNA, protein, cell) arrays. We are also interested in hyphenated devices with other conventional analytical instruments, and the pretreatment devices and components (valve, pump, etc.) for analysis/assay.